Displacement, diffusion and intensification (DDI) in marine fisheries: A typology for analyzing coalitional stability under dynamic conditions. Issue 54 (December 2015) - Blasiak, Robert; Doll, Christopher N.H.; Yagi, Nobuyuki; Kurokura, Hisashi
Graphical abstract: Highlights: Displacement, diffusion and intensification (DDI) of fisheries can be destabilizing. DDI often arises from the multi-year lag time in institutional response to change. Article introduces typology for DDI effects in marine capture fisheries. Examples from Atlantic mackerel, Alaska Pollock and Skipjack tuna fisheries. Balloon effects have been identified in range of different disciplines. Abstract: Achieving sustainable fisheries management often entails overcoming a range of substantial hurdles, particularly in the case of shared, straddling and highly migratory fish stocks. Gaps exist in ecological understanding of fish stocks, the number of fishing nations and their respective management practices are seldom static, and a range of natural and anthropogenic pressures can cause dramatic shifts in distribution and abundance of fish. Even for cases in which coalitions of fishing nations with coordinated management mechanisms exist, such pressures can introduce instability into the system. This paper describes the distinctions that can be drawn among the destabilizing effects caused by the reactive spatial displacement, diffusion or intensification (DDI) of fishing activities. A general typology of these effects is introduced based on phenomena observed in other policy areas and illustrated with specific examples from the Atlantic Mackerel, Alaska Pollock and Skipjack Tuna fisheries. These examples illustrate the contrast between fishing entities, which are flexible in swiftly reacting to changes in fisheries, while the institutional frameworks that exist to ensure sustainable management of fishery resources are remarkably slow. The multi-year lag time between the response of fishing entities and institutions is suggested as the main source of instability resulting from DDI effects. While this typology has not been previously applied to marine fisheries, the effects presented can be generalized to other policy areas to allow for a greater understanding of spatial effects along with their causes and consequences for the effectiveness of cooperation among partners and sustainable resource management.